Trocas gasosas e eficiência fotoquímica de plântulas de pinhão-manso (Jatropha curcas L.) em duas épocas no sertão de Alagoas - Souza, Felipe Cardoso (2014)
The physic nut is a species of oleaginous family of Euphorbia. Considered the most promising oil bearing crops as alternatives to the production of biodiesel in northeastern. The present work had as objective to evaluate the physiological behavior of the seedlings of the physic nuts, in dry season and in rainy season, grown in the semi-arid region of Alagoas. Assessed the percentage of deaths of seedlings in Craíbas and Santana do Ipanema crops. Were made daily evaluations of gas exchange using IRGA and photochemical efficiency through fluorometer. The incidence of deaths was high in both crops, caused due mainly to low rainfall in the first year after sowing, that was 258,62 mm in Santana do Ipanema and 485,6 mm in Craibas. The most photosynthesis time was in the morning,, dropping from 11:00 hours due mainly to the increase of the vapour pressure deficit that caused reduction in the stomatal conductance and consequently, the transpiration decreases. In dry season, at 13:00 hours, occurred the dynamic photoinhibition with a rapid recovery in the afternoon. These results show a certain adaptability of this species to the dry climate of the region, however where not sufficient to avoid the death of most the plants.